Predictors of insulin resistance among women with acne vulgaris and polycystic ovarian syndrome presenting to a tertiary care hospital in North India - Chandra, Mini; Vats, Koshinder; Garg, Palak; Tibrewal, Abhishek (International Journal of Research in Dermatology, 2021)
Background: Acne vulgaris is now being increasingly associated with hyperandrogenism or metabolic syndrome. The aim of the study was to know the burden and determinants of insulin resistance among females suffering from acne and polycystic ovarian syndrome (PCOS). Methods: This prospective observational study included non-pregnant females with acne and PCOS aged 14 to 36 years. PCOS was diagnosed using Rotterdam criteria. Insulin resistance (IR) was confirmed using HOMA-IR values. Important history was ascertained, and hormonal essays were done. SPSS version 22 was used for the analyses. Results: The average age of the 81 subjects was 22 (IQR: 19-23) years and median duration of acne was 8 (7-9) months. Their median (IQR) insulin level was 10.5 (8.4 - 18.5), fasting blood glucose was 82 (73.2 - 90) and HOMA-IR value was 2 (1.7 - 3.9). A total of 27 (33.3%) were diagnosed with IR. Subjects having IR had significantly lower FSH (median=3.1, IQR: 2.3-6.3), LH (3.0, 1.2-3.3) and insulin level (median=26.0, 18.5-28.5) versus those without IR (p=0.04, p=0.04 and p<0.001 respectively). Subjects with IR were more likely to be having irregular menses, weight gain, and acanthosis nigricans versus those without IR. Conclusions: One-third of the patients with acne and PCOS also had IR according to the HOMA-IR values. All women with acne and PCOS should be considered for underlying IR and examined for other sign of impaired glucose tolerance.